Conformation of D‐π‐A Molecular with Functional Imidazole Group: Achieving High Color Contrast Mechanochromic Behavior and Selectively Detection of Picric Acid in Aqueous Medium. Issue 24 (27th June 2019) - Zhang, Shuaishuai; Zhu, Huichao; Huang, Jianyan; Kong, Lin; Tian, Yupeng; Yang, Jiaxiang
Abstract: Multi‐stimuli responsive D‐π‐A molecular (named CZIZ ) comprising of carbazole as D, dicyano as A and imidazole as functional group was designed and synthesized. The photophysical properties showed that CZIZ possessed the property of aggregation‐induced emission enhancement (AIEE) property, which was verified by UV‐vis absorption and fluorescence spectra. In addition, the large twisted structure and loose arrangement induced CZIZ performed high color contrast mechanochromic (MC) behaviors from 537 nm to 584 nm, which was successfully applied in ink‐free rewritable paper. Furthermore, CZIZ showed high selective detection for picric acid (PA) in aqueous medium due to the excellent proton‐binding property of the imidazole group, which was verified by 1 H NMR spectra. The density functional theory verified that the fluorescent quenching mechanism is a photoinduced electron transfer (PET) process between CZIZ and PA. The compound CZIZ described herein will efficiently expand the development of design principles to supply diverse multifunctional tools for material science and material engineering. Abstract : D‐π‐A molecular (named CZIZ ) with functional imidazole group was designed and synthesized. CZIZ exhibited mechanochromic (MC) behaviors with high color contrast. Furthermore, CZIZ showed high selective detection for picric acid (PA) in aqueous medium due to the excellent proton‐binding property of the imidazole group.